Um estudo sobre a aplicabilidade do modelo MPLS/CBR no provimento de QoS numa rede IP - Araujo, Nelcileno Virgilio de Souza (2003)
The fast growth of the corporative users and the amount of real time applications in the Internet has demanded IP networks the creation of others Service models that can guarantee a differentiation of users traffíc and supply quality of Service in the transport of the packets. Following this trend, the IETF has presented diverse standardizations of Service models, such as integrated Services, differentiated Services, MPLS, constraint based routing and traffíc engineering, beyond the best effort Service. However, the isolated implementation of these models it has shown complex and, sometimes, inefficacious for determined situations. Therefore, the interoperation of Service models has been advised, since it gets each model, the most important functionality to generate a hybrid model. In this direction, this work presents and argues a Service model that combines CBR and technology MPLS. To evaluate the performance of this hybrid model in offering QoS, three parameters had been analyzed: throughput, delay and jitter. The results gotten in the simulated scenes had shown the viability of model MPLS/CBR in the construction of paths with QoS guarantees.